Workshop Pemanfaatan IT Dalam Rangka Peningkatan Kompetensi Guru Dan Pegawai MTs Negeri 6 Klaten, Jawa Tengah - Agustinus Suradi; Mahmud Yusuf; Aryati Wuryandari; Doni Setyawan (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
The use of IT in the learning process can provide great benefits, but awareness and understanding of the use of IT in the educational context still needs to be improved at MTs Negeri 6 Klaten. The aim of this workshop will be to provide opportunities for participants to understand and practice various IT applications that are relevant to the educational context. The PKM activity method is carried out in stages: observation & needs analysis, communication & dialogue, workshops, and evaluation. The results of this workshop activity can create a space for collaboration and exchange of ideas between teachers and staff, the material presented can be well understood by the majority of participants, namely 92%, and 96% of participants feel interested in the workshop material. So that it becomes a strategic step in improving the quality of education in MTs and providing better preparation for students in facing future challenges.